IMPLEMENTASI PROGRAM PERLINDUNGAN, PENGEMBANGAN, PEMELIHARAAN DAN PEMANFAATAN CAGAR BUDAYA DI PROVINSI SULAWESI TENGAH - Nurfaidah, Nurfaidah (Katalogis, 2018)
Cultural heritage is a legacy that needs to be preserved by protecting ang preserving objects and buildings of cultural heritage. Therfore, the government identifies the cultural heritage through the program of protection, development, maintenance and utilization of cultural heritage to be registered as a national cultural heritage. For that reason, the research was cunducted with the aim to see how the implementation of protegtin program, development, maintenance and utilization of heritage in central sulawesi province. The type of research used in this study is qualitative by using descriptive method. The informants in the study consistedd af head of department of education and culture of central sulawesi province, head of mission, 2 section heads and 2 staffs who are considered capable of providing answers to this research. Techniques of collecting and retrieving data consists of observation, interviews, and documentation. The theory used ini this research is the theory of policy implementation developed by Edward III. The resurts showed that from four aspects of policy implementation according to Edward III, there are aspects that looks good, namely the aspects of communication, disposition aspects and aspects of bureaucratic structure. While the aspect of resources is considered poor because of insufficient human resources in the implementation of registration and budget resources are very limited in supporting the implementation of the program